2022
DOI: 10.1128/spectrum.02580-22
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Bacterial Pathogens at Genus and Species Levels through Combination of Raman Spectrometry and Deep-Learning Algorithms

Abstract: In this study, we investigated 30 bacterial species belonging to 9 different bacterial genera that were isolated from clinical samples via surfaced enhanced Raman spectroscopy (SERS). A total of 17,149 SERS spectra were harvested from a Raman spectrometer and were further analyzed via machine learning approaches, the results of which showed that the convolutional neural network (CNN) deep learning algorithm could achieve the highest prediction accuracy for recognizing pathogenic bacteria at both the genus and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 31 publications
1
26
0
Order By: Relevance
“…coli . The result is consistent with previous studies, in which CNN model has been found to be the best for analyzing and predicting bacterial species ( Tang et al, 2021 ; Liu et al, 2022 ; Tang et al, 2022 ; Wang et al, 2022a,b ), though other machine learning algorithms such as SVM and RF also achieved very high levels of accuracy for species identification. Therefore, through this study, it was suggested that the label-free SERS technique coupled with machine learning algorithms could be used for the rapid discrimination of Shigella spp., and Escherichia coli .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…coli . The result is consistent with previous studies, in which CNN model has been found to be the best for analyzing and predicting bacterial species ( Tang et al, 2021 ; Liu et al, 2022 ; Tang et al, 2022 ; Wang et al, 2022a,b ), though other machine learning algorithms such as SVM and RF also achieved very high levels of accuracy for species identification. Therefore, through this study, it was suggested that the label-free SERS technique coupled with machine learning algorithms could be used for the rapid discrimination of Shigella spp., and Escherichia coli .…”
Section: Discussionsupporting
confidence: 91%
“…As an easy-to-learn, low-cost, non-invasive and label-free method, Raman spectroscopy, especially the surface enhanced Raman spectroscopy due to the significantly enhanced Raman signals, has great application potential for rapid and accurate bacterial pathogen identification in clinical settings, though huge challenges exist and the method has been officially used in real-world situation yet ( Wang et al, 2021 ). Previously, the promising SERS technique has been widely used for both genus/species discrimination and antibiotic resistance profiling in clinically important bacterial pathogens with rapid speed and high accuracy ( Ho et al, 2019 ; Tang et al, 2021 ; Liu et al, 2022 ; Tang et al, 2022 ; Wang et al, 2022a , b ). However, there is currently no reported of using label-free SERS technique coupled with machine learning algorithms for the differentiation of Shigella spp., and E .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By assessing the abundance of spectral features, we gained insights into each spectrometer's sensitivity and detection capabilities. Additionally, a shaded region representing 20% of the standard deviation (SD) was visualised around the average SERS spectra using Origin Software (OriginLab, United States) 17 . The software's fit peaks (pro) function was employed to automatically fit the spectral characteristic peaks, thereby identifying the corresponding molecular components.…”
Section: Methodsmentioning
confidence: 99%
“…16 Recent studies have increasingly employed SERS technology to detect microbial pathogens. 17,18 Yan et al 19 applied single-cell Raman spectrometry for rapid discrimination of 23 bacterial species across 7 genera. The study first utilized decision tree machine learning algorithms to assess and differentiate single bacterial cells at the serotype level and then constructed a quaternary classification model to elevate the accuracy of various recognition models, thus enabling efficient prediction of bacterial strains at the serotype level.…”
Section: Introductionmentioning
confidence: 99%